2012
DOI: 10.1111/j.1469-7998.2012.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Call acoustics reflect body size across four clades of anurans

Abstract: An inverse relationship between body size and advertisement call frequency has been found in several frog species. However, the generalizability of this relationship across different clades and across a large distribution of species remains underexplored. We investigated this relationship in a large sample of 136 species belonging to four clades of anurans (Bufo, Hylinae, Leptodactylus and Rana) using semi‐automatic, high‐throughput analysis software. We employed two measures of call frequency: fundamental fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
85
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 32 publications
9
85
0
4
Order By: Relevance
“…Body size is usually strongly correlated with spectral traits, and this correlation also holds between species, suggesting that fundamental and dominant frequencies are under morphological constraints, with smaller frogs (with shorter vocal cords) producing calls at higher frequencies (Gerhardt & Huber 2002;Gingras et al 2013). This correlation is almost universal in anurans, with few exceptions (Sullivan 1984;Sullivan & Malmos 1994;Lingnau & Bastos 2007), including frogs that can actively adjust frequency depending on the context (see above).…”
Section: Body Size and Individual Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Body size is usually strongly correlated with spectral traits, and this correlation also holds between species, suggesting that fundamental and dominant frequencies are under morphological constraints, with smaller frogs (with shorter vocal cords) producing calls at higher frequencies (Gerhardt & Huber 2002;Gingras et al 2013). This correlation is almost universal in anurans, with few exceptions (Sullivan 1984;Sullivan & Malmos 1994;Lingnau & Bastos 2007), including frogs that can actively adjust frequency depending on the context (see above).…”
Section: Body Size and Individual Recognitionmentioning
confidence: 99%
“…The spectral flatness, also known as tonality coefficient or Wiener entropy, is calculated as the geometric mean of the power spectrum divided by its arithmetric mean (Dubnov 2004). This measurement has not been tested so far as a tool for species delimitation in taxonomic approaches, but similar to dominant frequency, spectral flatness has been found to be inversely related to SVL in three of four frog clades studied (Gingras et al 2013).…”
Section: Dqlgdhmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that while many studies have found a relationship between fundamental frequency and body size in several species (e.g., Bowling et al, 2017;Charlton & Reby, 2016;Gingras, Boeckle, Herbst, & Fitch, 2013;Hauser, 1993;Wallschläger, 1980), others have not (e.g., Patel, Mulder, & Cardoso, 2010;Rendall, Kollias, Ney, & Lloyd, 2005;Sullivan, 1984). As noted by Bowling et al (2017), a relevant factor seems to be the range in body sizes 16 The authors theorize that two separate, but potentially related, processes may be at work.…”
mentioning
confidence: 99%
“…Because the vocal sac is inflated for the duration of the call, the duration of visible inflation of the vocal sac could provide redundant information to females on call duration, a frequent target of female choice in the acoustic modality (Gerhardt et al, 2000). In addition, the size of the vocal sac is likely to be correlated to overall male body size, a characteristic that is often correlated with the dominant frequency of acoustic signals (Gingras et al, 2013), but also potentially assessed visually by females. Finally, certain characteristics of vocal sacs may be signals that are entirely independent of the qualities assessed in the acoustic modality.…”
mentioning
confidence: 99%